Physical changes within a large tropical hydroelectric reservoir induced by wintertime cold front activity - Curtarelli, M. P.; Alcântara, E. H. [UNESP]; Rennó, C. D.; Stech, J. L. (Copernicus Publications, 2014)
We investigated the influence of wintertime cold front activity on the physical processes within a large tropical reservoir located in Brazil. The period chosen for this study consisted of 49 days between 28 April 2010 and 15 July 2010. This period was defined based on information from the Brazilian Center for Weather Forecasting and Climate Studies (CPTEC), data collected in situ and the interpretation of remotely sensed images. To better understand the governing processes that drive changes in the heat balance, differential cooling and mixing dynamics, a simulation was performed that utilized a three-dimensional hydrodynamic model enforced with in situ and remote sensing data. The results showed that during a cold front passage over the reservoir, the sensible and latent heat fluxes were enhanced by approximately 77 and 16%, respectively. The reservoir's daily averaged heat loss was up to 167% higher on the days with cold front activity than on the days without activity. The cold front passage also intensified the differential cooling process; in some cases the difference between the water temperature of the littoral and pelagic zones reached up to 8 °C. The occurrence of cold front passages impacted the diurnal mixed layer (DML), by increasing the turbulent energy input (~54%) and the DML depth (~41%). Our results indicate that the cold front events are one of the main meteorological disturbances driving the physical processes within hydroelectric reservoirs located in tropical South America during the wintertime. Hence, cold front activity over these aquatic systems has several implications for water quality and reservoir management in Brazil. © Author(s) 2014.